#TITLE_ALTERNATIVE# - Pringgoprawiro, Marsongkohadi
ABSTRACT: The magnetic structures of the transition metal nitrides, Fe4N and Mn4N were redetermined by unpolarized as well as polarized neutron scattering technique, in order to investigate the magnetic behaviour of the transition metal atoms in nonequivalent environments. The analysis of the unpolarized neutron diffraction profiles shows that Fe4N is a collinear ferromagnet, with room temperature magnetic moments of 2.7uB and 1.76 uB, for the corner and face-centre iron atoms, respectively. The corresponding values at 80 K are 2.90UB and 1.98PB respectively. On the other hand, Mn4N was found to be a collinear ferrimagnet with the corner manganese atom having a magnetic moment of 3.54UB, at room temperature (3.89UB at 80 K). This magnetic moment is directed along the magnetization which is opposed by the face-centre moments, each of which having a magnetic moment of -0.91UB at room temperature (-0.92 UB at 80 K). The present measurements are aimed at understanding not only the magnetic structures, but the magnetic form factors in these compounds, as well. The form factor of the face-centre iron atom is significantly expanded as compared to that of the corner iron atom, implying a contracted moment density for the face centre atom. The form factor obtained from the polarized neutron data for the face-centre manganese atom shows to be sharp. This suggest that the moment density for the face-centre Mn atom is more spread out than that of the corner atom. The experimentally determined moment densities have qualitatively been explained on the basis of an existing theoretical model. Another outcome of the present investigation is the discovery of polarizing reflections in Mn4N. Both the (100) and (110) reflections can produce almost 100% polarized monochromatic neutrons of opposite states of polarization. The resolution of the neutron diffractometer constructed for the present experiment was improved by selecting suitable values of divergences of the Soller collimators and the mozaic spread of the monochromator. Further improvements of the resolution was obtained by, selecting a suitable value of the ratio of the sourcetomonochromator distance and the monochromator to specimen distance. The magnet constructed for the present investigation provides a magnetic field of 1.0 T at a gap length of 3.4 cm. During the course of the experiment, the magnetic field should be maintained parallel to the scattering vector, while the magnet rotates in unison with the rotation of the spectrometers arm. The cryostat was constructed to maintain ea samples temperature of 80K continuously, during at least 240 hours, by refilling the liquid nitrogen every 24 hours, and the pressure of the vacuum chamber of the cryostat held at -6 x 106 Torr.